Application of solid surface fluorescence EEM spectroscopy for tracking organic matter quality of native halophyte and furrow-irrigated soils. (February 2017) - Pan, Hongwei; Yu, Huibin; Song, Yonghui; Liu, Ruixia; Du, Erdeng
Graphical abstract: Highlights: Develop solid surface EEM with PARAFAC to identify SOM components. Seek latent factors and reveal spatial distributions of SOM fractions by HCA. Deduce a humifcation index to assess humification levels of SOM. Abstract: Solid surface fluorescence excitation-emission matrix (EEM) is developed a potential method to characterize soil organic matter (SOM). Solid surface EEM spectroscopy with parallel factor analysis (PARAFAC) and hierarchical cluster analysis (HCA) is used to extract fluorescent components, to seek latent factors, and to investigate spatial distribution of SOM. Soil samples were collected from four native halophyte and two furrow-irrigated soil profiles, i.e. Comm. Salicornia europaea (CSE), Comm. Suaeda glauca (CSG), Comm. Kalidium cuspidatum (CKC), Comm. Sophora alopecuroides (CSA), corn fields (CFD), and wheat fields (WFD). SOM contained six fluorescent components: microbial/terrestrial fulvic-like fluorescent components (C1), tryptophan-like/lignin-derived phenol fluorescent components (C2), terrestrial humic-like fluorescent component (C3), lignin oxidative degradation by-products (C4 and C5), and amino acids (C6). The C 4 and C5 were the representative components of SOM within the CSE, CSG, CKC, CSA and CFD soil profiles, while the C2 and C6 were dominated within the WFD soil profile. The C4, C5, C1 and C2 were latent factors, and they could roughly distinguish SOM within the whole saline soil profiles except the CFD. A humification index (H/L) deduced from the fluorescent components, was very suitable to indicate humification levels of SOM. Humification levels of SOM within the halophyte soil profiles decreased with soil depth, but the opposite trends within the furrow-irrigated soil profiles. The H/L was closely correlated with exchangeable sodium percentage (ESP), and humification levels increased with the decreasing ESP. Soil surface EEM may not only indicate organic matter fractions of saline soils, but may be transferred to other types of landscape.